Porcine jejunal-derived extracellular vesicles participate in the regulation of lipid metabolism - Yaotian Fan; Haibin Deng; Jiahao Zhu; Junyi Luo; Ting Chen; Jiajie Sun; Yongliang Zhang; Qianyun Xi (Journal of Animal Science and Biotechnology)
Abstract Background Regulating the regional deposition of fat is crucial for improving the carcass characteristics of pigs. The intestine, as an important organ for lipid absorption and homeostasis maintenance, secretes various biological signals that participate in the crosstalk between the intestine and adipose tissue. Extracellular vesicles, as novel extracellular genetic factors that mediate metabolic signal exchange among multiple tissues, have emerged as a hotspot and breakthrough in revealing the mechanisms of physiological homeostasis. However, how extracellular vesicles regulate the intestinal-adipose signaling axis, especially in relation lipid metabolism and deposition is still unclear. Thus, in the current study, intestinal extracellular vesicles from Chinese fat-type piglets of Lantang and typical lean-type piglets of Landrace were isolated and identified, and to reveal the regulatory mechanisms of lipid metabolism via intestinal extracellular vesicles in mediating intestinal-adipose crosstalk. Results We isolated and identified intestinal extracellular vesicles from the jejunum of 3-day-old Lantang and Landrace piglets (LT-EVs and LD-EVs) and further investigated their effects on lipid accumulation in porcine primary adipocytes. Compared to LD-EVs, LT-EVs promoted lipid deposition in porcine primary adipocytes, with intestinal-derived miRNAs playing a critical role in the crosstalk between the intestine and adipose tissue. Further analysis of extracellular vesicles-derived miRNA sequencing revealed that miR-30b-5p, enriched in LD-EVs, is involved in the regulation of lipid metabolism. Notably, the enrichment of miR-30b-5p in extracellular vesicles derived from IPEC-J2 cells also influenced lipid metabolism. Mechanistically, the targeted binding of miR-30b-5p and FMO3 may be critical for the extracellular vesicle-mediated regulation of lipid metabolism. Conclusions Our findings suggest that jejunal-derived extracellular vesicles play a critical role in regulating lipid metabolism, and the regulatory effect of extracellular vesicles from obese piglets was higher than that of lean piglets. Furthermore, the different expression of miRNAs, such as miR-30b-5p, in intestinal extracellular vesicles may be the key to determining lipid deposition phenotypes across the two pig breeds. Graphical abstract